Discovery of novel CBP bromodomain inhibitors through TR-FRET-based high-throughput screening - Zhang Feng-cai; Sun Zhong-ya; Liao Li-ping; Zuo Yu; Zhang Dan; Wang Jun; Chen Yan-tao; Xiao Sen-hao; Jiang Hao; Lu Tian; Xu Pan; Yue Li-yan; et al. (Acta Pharmacologica Sinica, 2020)
The cAMP-responsive element binding protein (CREB) binding protein (CBP) and adenoviral E1A-binding protein (P300) are two closely related multifunctional transcriptional coactivators. Both proteins contain a bromodomain (BrD) adjacent to the histone acetyl transferase (HAT) catalytic domain, which serves as a promising drug target for cancers and immune system disorders. Several potent and selective small-molecule inhibitors targeting CBP BrD have been reported, but thus far small-molecule inhibitors targeting BrD outside of the BrD and extraterminal domain (BET) family are especially lacking. Here, we established and optimized a TR-FRET-based high-throughput screening platform for the CBP BrD and acetylated H4 peptide. Through an HTS assay against an in-house chemical library containing 20 000 compounds, compound DC_CP20 was discovered as a novel CBP BrD inhibitor with an IC50 value of 744.3 nM. This compound bound to CBP BrD with a KD value of 4.01 μM in the surface plasmon resonance assay. Molecular modeling revealed that DC_CP20 occupied the Kac-binding region firmly through hydrogen bonding with the conserved residue N1168. At the celluslar level, DC_CP20 dose-dependently inhibited the proliferation of human leukemia MV4-11 cells with an IC50 value of 19.2 μM and markedly downregulated the expression of the c-Myc in the cells. Taken together, the discovery of CBP BrD inhibitor DC_CP20 provides a novel chemical scaffold for further medicinal chemistry optimization and a potential chemical probe for CBP-related biological function research. In addition, this inhibitor may serve as a promising therapeutic strategy for MLL leukemia by targeting CBP BrD protein.